Effect of the Environmental, Social, and Governance on the Financial Performance of Mining Companies - Yanuarisya, Cindy; Wardianto, Kussuyatmono Bagus; Hasanah, Jamingatun (Journal of Business Management and Economic Development, 2025)
This study aims to analyze the influence of Environmental, Social, and Governance on financial performance. The research used is quantitative with secondary data. This study looks at 45 coal mining companies listed on the Indonesia Stock Exchange in 2020 to 2023 as its population. The purposive sampling method was used to select 12 companies as samples. The analysis technique used was panel data regression analysis, with E-views 12 as data processing software. The results of the study show that partially Environmental and Governance have a positive influence on financial performance (Tobin's Q) while Social partially has a negative influence on financial performance. Simultaneously, these three variables also have a significant effect on financial performance (Tobin's Q).